(untitled) (Semiárida, 2026)
Urban trees contribute significantly to achieving SDG 11, which focuses on sustainable cities. Therefore, it is important to further identify opportunities to strengthen the planning and management of urban green areas. To contribute to this goal, this study aimed to survey and analyse the state of urban trees in the Santa María de las Pampas neighbourhood, inaugurated in 2007 in the city of Santa Rosa, La Pampa. The area is located in the Espinal phytogeographic province and has a dry subhumid climate, with hot summers and cold winters. Using the Locus-GIS application, the following data were collected: species, height, growth site, condition, defects and previous management of the urban trees in the neighbourhood’s 29 city blocks. The data obtained were processed with GGIS program. A total of 1,282 potential tree-sites were identified, 438 without trees (34.2 %); the remaining 844 specimens were occupied mainly by exotic species, with a marked predominance of ash trees (57.3 % of the total), followed by privet (11.3 %), boxelder (5.2 %), and chinaberry (5.2 %). The height distribution reflected a young tree structure (0–5 m: 54.5 %; 5–10 m: 45.5 %); The majority of the trees exhibited characteristics of a soil-based growth site (64.0 %) and were in good condition (86.8 %), although 6.8 % showed signs of poor pruning. 98.1 % were without defects. The results showed a young tree population with low species richness and overuse of ash trees, highlighting the need to increase the number of trees and diversify the species used. Regarding management, it is essential that pruning practices be carried out by trained/authorized personnel and that any urban related damage to the trees be avoided.